A family of sweat pore-inspired compliant cellular expansion mechanisms. (May 2023) - Wang, Tingwei; Yu, Jingjun; Zhao, Hongzhe
Highlights: A family of compliant expansion mechanisms easy to tessellate is proposed. An accurate analytical model is developed via beam constraint model. A method to increase the amplification ratio via parameter design is introduced. Abstract: This paper proposes a family of sweat pore-inspired compliant cellular expansion mechanisms that has broad application prospects in the fields of metamaterial and new mechanism design. Compared with the existing counterparts, the proposed expansion mechanism is beneficial for achieving plane tessellation via cellular design, due to its regular polygonal structure. Based on the beam constraint model, an accurate analytical model for the expansion mechanism is developed. According to the analytical model, performances of the expansion mechanism such as displacement amplification ratio and input compliance are analyzed, and a simple approach to maximize the amplification ratio is proposed. The relations between amplification ratio and design parameters such as angle, thickness-length ratio, number of edges, and input force are obtained by analytical model and verified by finite element analysis, which shows that the average deviations of the analytical model are less than 0.95%.